Penggunaan Kamus Dwibahasa Sebagai Sumber Belajar Dalam Penguasaan Kosakata Bahasa Arab Mahasiswa Prodi Biologi UINSU Medan - Lubis, Farhan Mubarok; Zaini, Hisyam (LPPPI Publishing, 2024)
This research aims to explore the use of bilingual dictionaries as a learning resource in mastering Arabic vocabulary by Biology Study Program students at the North Sumatra State Islamic University (UINSU) Medan. The background to this research is based on the importance of mastering Arabic vocabulary in supporting understanding of religious and scientific literature, especially in the UINSU academic environment which integrates Islamic knowledge and science. The research method used is a qualitative descriptive method with a case study approach. Data was obtained through interviews, observations, and Google forms given to students as well as analysis of related documents. The research results show that the use of a bilingual dictionary significantly helps students understand and expand their Arabic vocabulary. Bilingual dictionaries are effective tools in the learning process, facilitating the translation of technical and scientific terms, as well as improving communication skills in Arabic. This research concludes that the integration of the use of bilingual dictionaries in the curriculum and teaching and learning activities is highly recommended to improve Arabic language mastery of Biology Study Program students at UINSU Medan.